Open country, Iowa : rural women, tradition and change - Fink, Deborah, 1944- (State University of New York Press, 1986)
Aan de hand van de levensgeschiedenissen van vrouwen wordt de hedendaagse situatie van boerinnen in Iowa (V.S.) geschetst.
Keywords: Börngen, ...; Rural women -- Iowa -- Case studies.; Women -- Iowa -- Case studies.; Rural women -- United States -- Case studies.; Femmes en milieu rural -- Iowa -- Études de cas.; Femmes -- Iowa -- Études de cas.; Femmes en milieu rural -- États-Unis -- Études de cas.; SOCIAL SCIENCE -- Women's Studies.; Rural women; Women; Iowa; United States; Ländlicher Raum; Landfrau; Frau; Femmes -- Etats-Unis -- Iowa.; Femmes en milieu rural -- Etats-Unis -- Iowa.; Electronic books.; Case studies; Case studies.; Études de cas.